2022
DOI: 10.1038/s41467-022-28456-9
|View full text |Cite
|
Sign up to set email alerts
|

A metal-supported single-atom catalytic site enables carbon dioxide hydrogenation

Abstract: Nitrogen-doped graphene-supported single atoms convert CO2 to CO, but fail to provide further hydrogenation to methane – a finding attributable to the weak adsorption of CO intermediates. To regulate the adsorption energy, here we investigate the metal-supported single atoms to enable CO2 hydrogenation. We find a copper-supported iron-single-atom catalyst producing a high-rate methane. Density functional theory calculations and in-situ Raman spectroscopy show that the iron atoms attract surrounding intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
113
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 64 publications
2
113
0
Order By: Relevance
“…Experimentally, several Cu-based SAA catalysts doped with TMs from the VIIIB group have been successfully synthesized. [41][42][43][44][45] However, there are greater spaces of SAAs through doping TMs from other elements. In this work, we built the theoretical models of Cu-based SAA catalysts using 18 TMs from the VB to VIIIB groups (3d: V, Cr, Mn, Fe, Co, Ni; 4d: Nb, Mo, Tc, Ru, Rh, Pd; 5d: Ta, W, Re, Os, Ir, Pt), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, several Cu-based SAA catalysts doped with TMs from the VIIIB group have been successfully synthesized. [41][42][43][44][45] However, there are greater spaces of SAAs through doping TMs from other elements. In this work, we built the theoretical models of Cu-based SAA catalysts using 18 TMs from the VB to VIIIB groups (3d: V, Cr, Mn, Fe, Co, Ni; 4d: Nb, Mo, Tc, Ru, Rh, Pd; 5d: Ta, W, Re, Os, Ir, Pt), as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of single atom catalysts (SACs) was first introduced by Zhang and coworkers in 2011, where a single atomic layer of platinum was incorporated into an iron oxide support. [4] Since then, SACs have been utilized to catalyse several reactions such as water oxidation, [5][6][7] CO 2 reduction [8][9][10] and hydrogenation, [11,12] oxygen reduction, [13][14][15] hydrogen evolution, [7,[15][16][17][18] among others. [7,[19][20][21][22][23] Zhang and co-workers also synthesized a mixed gold and palladium SAC, which was supported on ion exchange resins and used to catalyse Ullmann reaction [24] of aryl halides in an aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, carbon materials as substrates not only provide anchor points for single metal atoms, but also change the charge density and electronic structure of metal atoms due to the strong interface interaction between metal atoms and adjacent carbon atoms [18] . New electronic metal‐support interaction is involved when the carbon materials with metal atoms introduced act as substrates to support metal nanocrystals, which enhancing the stability of the catalyst in the HER reaction while ensuring the activity of the catalyst [19] . This metal support interaction (MSI) is the focus of metal carbon‐based catalysts in recent years, and studies have found that when the size of metal nanoparticles is reduced to the single atom level, the MSI will be maximized, resulting in new catalytic active sites and finally improve the catalytic performance [20] …”
Section: Introductionmentioning
confidence: 99%
“…[18] New electronic metal-support interaction is involved when the carbon materials with metal atoms introduced act as substrates to support metal nanocrystals, which enhancing the stability of the catalyst in the HER reaction while ensuring the activity of the catalyst. [19] This metal support interaction (MSI) is the focus of metal carbon-based catalysts in recent years, and studies have found that when the size of metal nanoparticles is reduced to the single atom level, the MSI will be maximized, resulting in new catalytic active sites and finally improve the catalytic performance. [20] Importantly, a significant advantage of atomically dispersed metal carbon-based catalysts is that the structurally uniform and well-defined single atomic site is an ideal model system for providing atomic-level insight into active sites and the corresponding catalytic reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%